PENGARUH PENDAPATAN DAERAH DAN PEMBIAYAAN TERHADAP BELANJA MODAL KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Angreini, Fitri; Sari, Kartika Rachma; Dwitayanti, Yevi (P3M Politeknik Negeri Banjarmasin, 2022)
This study examines the effect of income and financing on district/city capital expenditures in South Sumatra Province from 2018 to 2020. Researchers used secondary data from the website of the Directorate General of Fiscal Balance and the Supreme Audit Agency of South Sumatra Province. Thirty samples used in this study were determined by purposive sampling. Multiple linear regression and descriptive statistics were used to test the data using SPSS. Based on the results of the study, it can be said that partially PAD and transfer income have an effect on capital expenditure, while other legitimate regional income, financing receipts, and financing expenditures have no effect on capital expenditure. Simultaneously, PAD, transfer revenue, other legitimate regional revenues, financing receipts, and financing expenditures have a positive and significant effect on capital expenditures